Інтертекстуальність у поетичній мовотворчості Максима Рильського - Палаш, А. (Культура слова, 2020)
У статті запропоновано дослідження особливостей реалізації
інтертекстуальності в поезіях Максима Рильського; простежено
поняття «інтертекст» у широкому та вузькому розумінні;
схарактеризовано класифікацію інтертекстуальності Ж. Женнет.
Здійснено аналіз міжтекстових зв’язків, спостережених у
мовотворчості Максима Рильського. Диференційовано та описано
такі різновиди інтертекстуальних компонентів, як цитата, алюзія,
натяк, жанровий зв’язок текстів, посилання на власний передтекст
(самоцитація, самоповтор).
Вияви інтертекстуальності відзначено і на внутрішньо-
текстовому рівні, і в епітекстових позиціях (заголовок, епіграф). Problem’s setting. The problem of interpretation and research of
the term “intertextuality” today is a topical issue of philosophy, literary
criticism, linguistics, modern Ukrainian linguistic poetics, and stylistics of
the text. That is, no text can be created in an empty space, it must have an
intertextual relationship with other works or texts.
Analysis of recent studies. The theoretical basis for the study formed
works in the field of modern linguistics, in particular, Robert de Bogrand,
Alexander Veselovsky, Olga Vorobyova, Wolfgang Dressler, Alexander
Potebnya considered “intertextuality” as a textual category; Yuri Lotman,
Vladimir Lukin – as a prerequisite for textuality; Lyudmyla Babenko,
Suren Zolyan, Larysa Omelchenko, Natalia Fateeva – as means of its
implementation in specific texts.
Objective of the research. The purpose of the work is to analyze the
external and internal connections of the literary text of Maksym Rylsky
and the means of their realization in the explicitly intertextual process of
the text’s existence.
The main part. The article studies the peculiarities of the artistic
embodiment of intertextuality in the poems of Maxim Rylsky; the definition
of intertext in a broad and narrow sense is traced; the classification of the
intertextuality of Jennet is singled out. The focus is on the separation
of language units, intertextual components in the language of Maxim
Rylsky; examples and quotations, allusions, titles, epigraphs, hints, genre
connection of texts, references to the pretext in the artist’s creative work
are given and analyzed.
Conclusions. Research and analysis of the intertextuality of the
artist’s poetics show that in a new way the comprehension and depiction
of quotations, allusions, epigraphs, titles, hints, paraphrases become
differential features of the individual author’s style.